Helius Sjamsuddin and Suhartono W. Pranoto in Indonesian Historical Methodology: Conceptual Critique of Method and Methodology - Priyadi, Sugeng (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This article examines how Helius Sjamsuddin and Suhartono W. Pranoto conceptualized historical methodology in comparison with the methodological legacy of Sartono Kartodirdjo and Kuntowijoyo. Kartodirdjo’s pioneering contribution lay in distinguishing historical methodology from historical method and in developing a multidimensional social-science approach rooted in the first National History Seminar and his dissertation research. Using the historical method (heuristics, criticism, interpretation, and historiography), this study treats Sjamsuddin’s Metodologi Sejarah (2007) and Pranoto’s Teori & Metodologi Sejarah (2010) as intellectual-history sources. The findings show that both works combine historical method and historical methodology within single reference books, thereby obscuring the distinction between practical research procedures and theoretical reflection. Although both historians contributed to the teaching of historical studies, their works give limited attention to historical theories, concepts, and approaches derived from auxiliary sciences. This article argues for a clearer separation between historical method as practice and historical methodology as theory.